2018
DOI: 10.1177/1532708618817880
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Inclusion: Theorizing “Abjectivity” and Agency Under DACA

Abstract: Critical migration scholars argue that undocumented 1.5-generation immigrants occupy distinct forms of “abject” statuses, as legally excluded yet physically included members of society. Implemented in June 2012, the Deferred Action for Childhood Arrivals (DACA) program promised to alleviate the situation of many undocumented young persons in the United States by providing them with temporary work authorization, social security numbers, and protection from deportation. Using critical psychological theory, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This has also been characterized as entrapment in a “jaula de oro” (Los Tigres del Norte, 1984), a “golden cage” where there is but the “illusion of freedom” (Pérez Huber, 2015, p. 94). Ellis et al (2019) described this liminality as “legal abjectivity” in reference to how “partially inclusive immigration policies can (re)create liminal subjectivities” (p. 161). Even as policies reduce and relax constraints, “these young persons continued to feel excluded, fearful, and uncertain about their futures,” and “their new status could not relieve them from their experiences of abjectivity” (Ellis et al, 2019, p. 168).…”
Section: Constraints and Uncertainty For Undocumented Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has also been characterized as entrapment in a “jaula de oro” (Los Tigres del Norte, 1984), a “golden cage” where there is but the “illusion of freedom” (Pérez Huber, 2015, p. 94). Ellis et al (2019) described this liminality as “legal abjectivity” in reference to how “partially inclusive immigration policies can (re)create liminal subjectivities” (p. 161). Even as policies reduce and relax constraints, “these young persons continued to feel excluded, fearful, and uncertain about their futures,” and “their new status could not relieve them from their experiences of abjectivity” (Ellis et al, 2019, p. 168).…”
Section: Constraints and Uncertainty For Undocumented Studentsmentioning
confidence: 99%
“…Ellis et al (2019) described this liminality as “legal abjectivity” in reference to how “partially inclusive immigration policies can (re)create liminal subjectivities” (p. 161). Even as policies reduce and relax constraints, “these young persons continued to feel excluded, fearful, and uncertain about their futures,” and “their new status could not relieve them from their experiences of abjectivity” (Ellis et al, 2019, p. 168). In this regard, it is possible that financial aid policies absent a pathway to citizenship may only lead to small shifts in course enrollment decisions or no shifts at all.…”
Section: Constraints and Uncertainty For Undocumented Studentsmentioning
confidence: 99%
“…Despite this, with court challenges, sustained organizing and shifting immigration priorities, as of May, 2021, DACA remains in effect. Being DACAmented positioned certain groups of undocumented youth in a partially included liminal or "abject" status but with new modes of agency and resistance [16]. Part of these new modes of agency and resistance took the form of countering invisibility, as C discusses below.…”
Section: Countering Invisibilitymentioning
confidence: 99%
“…For more than a decade, critical migration scholars have shown that restrictive and inhospitable immigration contexts shape irregular migrants' social and material conditions as well as their everyday psychosocial well-being and modes of ''beingin-the-world'' (Bloch et al 2014;De Genova 2002;Ellis, Gonzales, and Rendón García 2018;Gonzales 2016;Gonzales and Chavez 2012;Willen 2007aWillen , 2014. 1 Migrant 'illegality' is a sociopolitical condition produced by the multiplication of everyday borders (Balibar 2004) and by ''deportability'' (De Genova 2002)-the process by which belonging is demarcated and exclusion generated.…”
Section: Introductionmentioning
confidence: 99%
“…The current management of irregular migrants in Norway distinguishes between lives that are to be enhanced and lives that are not worth preserving (Das and Das 2007). This contributes to an exclusive politics of belonging (Yuval-Davis 2011) as it situates irregular migrants outside what Andrews (1999) calls the ''political economy of hope'': the idea that in a free market economy, everyone can succeed under certain conditions.Though irregular migrants are socialized into irregularity (Bloch et al 2014), they find ways of exercising various modes of agency and attain degrees of control and resistance (Bloch et al 2014;Ellis and Rendón 2018;Bendixsen 2018) that allow them to re-establish a sense of belonging.…”
Section: Introductionmentioning
confidence: 99%